1999
DOI: 10.1046/j.1365-2567.1999.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and translocation of Rac2 in eosinophils during superoxide generation

Abstract: Eosinophils induce tissue injury by releasing granule-associated cytotoxic proteins, lipid mediators and superoxide anions in response to appropriate stimuli. Superoxide generation associated with respiratory burst is largely dependent on the assembly of the NADPH oxidase complex in the membrane, consisting of membrane-bound cytochrome b558 and translocated p47phox and p67phox. The activation of this complex is critically dependent on the translocation of GTP-bound Rac1, or its homologue Rac2, from the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…However, in bone marrow-derived Rac2 Ϫ/Ϫ neutrophils, the superoxide production in response to IgG-coated SRBC or fMLP was significantly abrogated, suggesting the important role of Rac2 in the function downstream of chemoattractant and Fc␥R (42). In addition, Lacy et al (43) have shown that Rac2 translocates from cytosol to plasma membrane-associated fractions along with p47phox and p67phox in PMA-stimulated eosinophils.…”
Section: Discussionmentioning
confidence: 98%
“…However, in bone marrow-derived Rac2 Ϫ/Ϫ neutrophils, the superoxide production in response to IgG-coated SRBC or fMLP was significantly abrogated, suggesting the important role of Rac2 in the function downstream of chemoattractant and Fc␥R (42). In addition, Lacy et al (43) have shown that Rac2 translocates from cytosol to plasma membrane-associated fractions along with p47phox and p67phox in PMA-stimulated eosinophils.…”
Section: Discussionmentioning
confidence: 98%
“…The molecular mechanisms associated with NADPH oxidase assembly and activation have been studied in more detail in neutrophils (5, 8, 10 -13) and cell-free assays (10,14) than in eosinophils (15)(16)(17)(18)(19). This complex is composed of five essential subunits, the membrane-bound cytochrome b 558 (a complex of two subunits, p22 phox and gp91 phox ) which associates with cytosolic subunits Rac, p47…”
Section: Divergence Of Mechanisms Regulating Respiratory Burst In Blomentioning
confidence: 99%
“…Generation of extracellular O 2 -from cells in suspension was measured as previously described (19). Briefly, cells (1-2 ϫ 10 6 ) were suspended in 1-ml microcuvets containing supplemented PBS (PBS ϩ ), pH 7.4 (with 1.2 mM MgCl 2 , 5 mM KCl, 0.5 mM CaCl 2 , 5 mM glucose, and 0.1% BSA) and 50 M ferricytochrome c at 25°C.…”
Section: Measurement Of O 2 -Release From Eosinophilsmentioning
confidence: 99%
See 2 more Smart Citations